Mortgage Finance and Technological Change - Robin Döttling; Enrico Perotti (Tinbergen Institute, 2015)
We explore how house prices evolve under technological progress, when housing serves for consumption as well as store of value. Technological change leads to human capital substituting physical capital and manual labor. Reduced use of physical capital implies that firms have less tangible collateral to pledge for external finance. This results in lower business demand for credit and a decline in interest rates. Over time, savings are redirected to mortgage credit, where houses serve as collateral. Under fixed land supply, house prices rise in real terms. The combination of growing wage inequality and mortgage credit leads to high household leverage for low-skill workers, increasing default rates and foreclosures. Restraining mortgage borrowing is more effective than subsidies to limit mortgage defaults, by containing both leverage and house price appreciation. It also leads to lower interest rates, supporting more corporate investment and higher wages.
Keywords: D33; E22; E44; R21; 330; Inequality; mortgage credit; housing; human capital; skill-biased technological change